ASUHAN KEBIDANAN MASA NIFAS DI PRAKTIK MANDIRI BIDAN SALABIAH KECAMATAN BANDA SAKTI KOTA LHOKSEUMAWE - Sari, Muliana; Nurmila (JURNAL KESEHATAN ALMUSLIM, 2023)
From the Registration of the Family Health Program at the Ministry of Health in 2020 it shows 4,6257 deaths in Indonesia. This number shows an increase compared to 2019 of 4,221 deaths. Based on the causes, most of the maternal deaths in 2020 were caused by 1,330 cases of bleeding, 1,110 cases of hypertension during pregnancy and 230 cases of circulatory system disorders. Objective ; Able to provide midwifery care for postpartum mothers at PMB Salabiah, Banda Sakti District, Lhokseumawe City according to midwifery service standards using varney midwifery management and documented with the SOAP method. Type of report in the form of a case, carried out at PMB Salabiah, Banda Sakti District, Lhokseumawe City from 19 December 2021 to 2 January 2022. Subject is Mrs. Z aged 26 years with P2A1, HPHT March 02, 2021, TTP December 29, 2021 . Postpartum care visits for Mrs. Z were carried out 3 times, namely visit 1 carried out on December 19, 2021 and found results with patients with grade II perineal rupture lacerations, midwives treated heactin wounds. Visit II was carried out on December 25, 2021, the results of the laceration wound were starting to dry. The care given was counseling about personal hygiene and visit III on December 31, 2021, the heacting wound was starting to dry, the care given was personal hygiene, all care given was according to midwifery care standards . It is expected that patients will always have awareness that the importance of health during the puerperium is to prevent maternal death.